Impactos da religiosidade e espiritualidade na adesão ao tratamento e qualidade de vida de pacientes ambulatoriais com insuficiência cardíaca - AZEVEDO, Kaline Silva (2022)
Heart Failure (HF) is a serious global public health problem. It is estimated that 64.3 million people worldwide experience this chronic condition. Studies indicate that the prevalence of HF in first world countries is around 1% to 2% of the general adult population. In Brazil, 01 in 05 people will develop Heart Failure (HF), which is the most common responsible for hospitalization of people over 65 years old. Even with the important progress in the clinic and treatment of HF, this condition is still challenging due to all the physical, emotional and social discomfort, as a result of the limitations it triggers, and changes in life habits necessary to maintain quality of life. Given this reality, studies have pointed to an increase in the number of studies that seek to assess the influences of spirituality in the way individuals deal with their physical and mental health. Quality of life is an important aspect of the life of patients with HF. This research sought to evaluate spirituality/religiosity and adherence to treatment and quality of life in outpatients with HF in São Luís-MA. This is a crosssectional analytical study, carried out in the premises of the Heart Failure Outpatient Clinic, located in the Maternal and Child Unit of the University Hospital of the Federal University of Maranhão, in the city of São Luís-MA, with 42 patients over 18 years of age, diagnosed with IC with functional classification between I and IV, with care at the aforementioned outpatient clinic for at least 03 months. Five instruments validated in Brazil were used to verify three aspects: adherence to treatment, quality of life and the patient's degree of spirituality and religiosity. With the extraction of the average of the scores of the instruments and their analyses, the prevalence of spirituality and religiosity, quality of life and adherence to treatment of the studied sample were estimated. The study revealed that an organized religious practice and a strong intrinsic religiosity. As for aspects related to treatment adherence, patients showed a positive mean of adherence.